2017
DOI: 10.1016/j.kjms.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of sugammadex for general anesthesia and facial nerve monitoring in patients undergoing parotid surgery

Abstract: The use of neuromuscular blocking agent (NMBA) during anesthesia may interfere with facial nerve monitoring (FNM) during parotid surgery. Sugammadex has been reported to be an effective and safe reversal of rocuronium-induced neuromuscular block (NMB) during surgery. This study investigated the feasibility and clinical effectiveness of sugammadex for NMB reversal during FNM in Parotid surgery. Fifty patients undergoing parotid surgery were randomized allocated into conventional anesthesia group (Group C, n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 22 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…During monitored parotid or thyroid surgery, a dose of 2 mg/kg sugammadex could induce nearly complete NMB recovery within 10 minutes. 17,19 Since muscle relaxation is also required during surgery, complete neuromuscular function recovery may not be the best management protocol. The main purpose of this study was to investigate suitable dosage and timing of sugammadex administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During monitored parotid or thyroid surgery, a dose of 2 mg/kg sugammadex could induce nearly complete NMB recovery within 10 minutes. 17,19 Since muscle relaxation is also required during surgery, complete neuromuscular function recovery may not be the best management protocol. The main purpose of this study was to investigate suitable dosage and timing of sugammadex administration.…”
Section: Discussionmentioning
confidence: 99%
“…Sugammadex as an antagonist to steroidal NMBA is applied in patients requiring IONM during thyroid or parotid surgery. [17][18][19] There is a controversy between routine and selective reversal of NMB with sugammadex in monitored thyroidectomy. In our previous study, we confirmed a routine fully-NMB-reversal protocol with sugammadex (2 mg/kg) provided both excellent intubation condition and high initial EMG signal of IONM in 100% of 50 patients.…”
Section: Introductionmentioning
confidence: 99%
“…These days, many surgical procedures require intraoperative neuromonitoring using a neural integrity monitor. In the case of ear, nose, and throat surgery, facial or recurrent laryngeal nerve monitoring is required for NMB reversal and sugammadex can be an option for the rapid and effective reversal from rocuronium-induced deep NMB [ 98 100 ].…”
Section: Recent Clinical Interests Regarding Sugammadexmentioning
confidence: 99%
“…49 In addition, sugammadex can also be used at any stage of surgery to reverse deep neuromuscular block when IONM is necessary. 35,50,51 However, the regimen (routine/selective) and even dose of sugammadex for neural monitoring remains debatable. 52,53 35,50,51,[54][55][56] A protocol of sugammadex 2 mg/kg at skin incision rapidly restores neuromuscular function suppressed by rocuronium 0.6 mg/ kg at anesthesia induction.…”
Section: Rocuronium Combined With Sugammadexmentioning
confidence: 99%
“…35,50,51 However, the regimen (routine/selective) and even dose of sugammadex for neural monitoring remains debatable. 52,53 35,50,51,[54][55][56] A protocol of sugammadex 2 mg/kg at skin incision rapidly restores neuromuscular function suppressed by rocuronium 0.6 mg/ kg at anesthesia induction. All patients receiving routine regimen showed high initial EMG amplitude at initial vagal (V1) stimulation, which was vital for surgical decision and nerve injury evaluation during monitored thyroidectomy.…”
Section: Rocuronium Combined With Sugammadexmentioning
confidence: 99%